Managing Migration and Asylum Issues in the European Space: among Multi-level Governance and the Securitization Options - Derradji, Hichem (Technium Social Sciences Journal, 2022)
This study seeks to monitor and analyze the most prominent European policies related to immigration and asylum issues, as these policies have known over the past two decades many contradictions expressed by these different options at all levels. European space decision-makers have often chosen the multi-level governance path to integrate migrants and refugees into European societies. In contrast, at other times, security policy and selection have led to results effectively reflected in high hatred towards immigrants and refugees.